Characterization of Maltase and Sucrase Inhibitory Constituents from Rhodiola crenulata - Li, Wen-Tai (Foods, 2019)
The inhibitory properties of epicatechin-(4β,8)-epicatechingallate (B2-3’-O-gallate), epicatechin gallate (ECG), and epicatechin (EC) isolated from Rhodiola crenulata toward maltase and sucrase were investigated. The half-maximal inhibitory concentration (IC(50)) values for maltase were as follows: B2-3’-O-gallate (1.73 ± 1.37 μM), ECG (3.64 ± 2.99 μM), and EC (6.25 ± 1.84 μM). Inhibition kinetic assays revealed the inhibition constants (Ki) of the mixed-competitive inhibitors of maltase, as follows: B2-3’-O-gallate (1.99 ± 0.02 μM), ECG (3.14 ± 0.04 μM), and EC (7.02 ± 0.26 μM). These compounds also showed a strong inhibitory activity toward sucrase, and the IC(50) values of B2-3’-O-gallate, ECG, and EC were 6.91 ± 3.41, 18.27 ± 3.99, and 18.91 ± 3.66 μM, respectively. Inhibition kinetic assays revealed the inhibition constants (Ki) of the mixed-competitive inhibitors of sucrase as follows: B2-3’-O-gallate (6.05 ± 0.04 μM), ECG (8.58 ± 0.08 μM), and EC (13.72 ± 0.15 μM). Overall, these results suggest that B2-3’-O-gallate, ECG, and EC are potent maltase and sucrase inhibitors.